Childhood muscle morphology and strength: Alterations over six months of growth. - Pitcher, C.; Elliott, Catherine; Williams, Sian; Licari, M.; Kuenzel, A.; Shipman, P.; Valentine, J.; Reid, S. (John Wiley and Sons, 2012)
Introduction: The purpose of this study was toestablish the nature and stability of the strength-size relationship for the knee flexors and extensors across a 6-month period of childhood growth. Methods: Nineteen typically developing children aged 5–11 years underwent lower limb magnetic resonance imaging (MRI) and dynamometry strength assessments on 2 occasions, 6 months apart. Muscle volume (MV) and maximum anatomical cross-sectional area (aCSA) for the knee flexors and extensors were determined using MRI analysis software. Isokinetic dynamometry determined corresponding isometric and isokinetic strength. Results: Strong correlations were found between muscle size and strength for both the knee flexors and extensors (r ¼ 0.84–0.90; P < 0.01). Furthermore, the ratio of strength to muscle size remained consistent across 6 months of prepubescent growth. Conclusions: Increases in thigh muscle strength were relative to those in muscle size,suggesting that muscle growth may play an important role in the development of strength during childhood.